2005
DOI: 10.1042/cs20050088
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral delivery of the β2-adrenoceptor gene in sepsis: a subcutaneous approach in rat for kidney protection

Abstract: Successful gene therapy requires gene delivery that is efficient, has an optimal route of administration and has biosafety. The aims of the present study were to evaluate the safety and applicability of the subcutaneous delivery route for adenoviral transgenes containing the human beta(2)-adrenoceptor (adeno-beta(2)-AR) and to investigate whether this approach prevented renal dysfunction in a rat model of endotoxaemic shock induced by LPS (lipopolysaccharide). Subcutaneous administration of adeno-beta(2)-AR (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…We demonstrated that RPTC b 2 AR is responsible for the effects of formoterol on renal function after AKI. Previous studies in septic AKI demonstrated that overexpression or activation of the b 2 AR by terbutaline prevents apoptosis, decreases injury, and promotes recovery of renal function (Nakamura et al, 2003(Nakamura et al, , 2004(Nakamura et al, , 2005(Nakamura et al, , 2010; however, in these studies, excessive activation of the b 2 AR decreased serum creatinine (Nakamura et al, 2007). We have shown that selective and limited activation of the b 2 AR by formoterol accelerates recovery from IR-induced AKI (Jesinkey et al, 2014), and in these studies, we have shown that formoterol does so by activating RPTC b 2 AR.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that RPTC b 2 AR is responsible for the effects of formoterol on renal function after AKI. Previous studies in septic AKI demonstrated that overexpression or activation of the b 2 AR by terbutaline prevents apoptosis, decreases injury, and promotes recovery of renal function (Nakamura et al, 2003(Nakamura et al, , 2004(Nakamura et al, , 2005(Nakamura et al, , 2010; however, in these studies, excessive activation of the b 2 AR decreased serum creatinine (Nakamura et al, 2007). We have shown that selective and limited activation of the b 2 AR by formoterol accelerates recovery from IR-induced AKI (Jesinkey et al, 2014), and in these studies, we have shown that formoterol does so by activating RPTC b 2 AR.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 30 years, many methods have been proposed to deliver exogenous genes and cells to target organs [31,38,45,95,98,100,128,140,[147][148][149][150][151][152][153][154][155]. From a fundamental viewpoint, these techniques seek to provide inexpensive and rapid alternatives to pronuclear microinjection-derived transgenic models and platforms for translational studies [119].…”
Section: The Development Of Efficient Delivery Techniquesmentioning
confidence: 99%
“…Several reports have indicated inconsistent outcomes regarding the effectiveness of existing gene and cell transfer techniques. Studies in the kidney have illustrated this variability [153,154,[156][157][158][159][160][161][162]. In general, an in vivo gene and cell transfer system's success relies on various factors.…”
Section: The Development Of Efficient Delivery Techniquesmentioning
confidence: 99%
“…Over the past 30 years, many methods have been proposed to deliver exogenous genes and cells to target organs (32,39,46,97,100,102,130,142,(149)(150)(151)(152)(153)(154)(155)(156)(157). From a fundamental viewpoint, these techniques seek to provide inexpensive and rapid alternatives to pronuclear microinjection-derived transgenic models and platforms for translational studies (121).…”
Section: Key Aspects To Facilitate Advancements In Renal Genetic Medi...mentioning
confidence: 99%
“…Several reports have indicated inconsistent outcomes regarding the effectiveness of existing gene and cell transfer techniques. Studies in the kidney have illustrated this variability ( 155 , 156 , 158 164 ). In general, an in vivo gene and cell transfer system’s success relies on various factors.…”
Section: Key Aspects To Facilitate Advancements In Renal Genetic Medi...mentioning
confidence: 99%